Distrofia ungueal subclínica em pacientes com psoríase: existe papel para a ultrassonografia ungueal? - Klemz, Barbara Nascimento De Carvalho [UNIFESP] (2018)
Objectives: To verify the association between ultrasonographic findings and joint involvement in patients with psoriasis, and to assess if any clinical, laboratorial or imaging aspect could be associated with the arthritis involvement over time. Patients and Methods: A total of 56 patients with psoriasis (Ps) were enrolled in this casecontrol study with 2 evaluations, including at baseline and 4 years later. They were categorized into two groups according to nail dystrophy (ND). In addition, 30 healthy controls (HC) were paired by sex, age and body mass index (BMI). Patients with a previous diagnosis of any rheumatic disease or with paronychia, anonychia, painted nails or onychophagia were excluded. PASI (Psoriasis Area Severity Index), NAPSI (Nail Psoriasis Severity Index), PASE (Psoriatic Arthritis Screening and Evaluation) and PEST (Psoriasis Epidemiology Screening Tool) were applied by a dermatologist. The rheumatologic evaluation, including dactylitis, enthesitis, arthritis, axial disease, and the CASPAR (ClASsification criteria for Psoriatic ARthritis) criteria were carried out by a rheumatologist. A third observer blinded for the other assessments performed the ultrasound of the joints, enthesis, skin and nails, by using MyLab70® (Esaote, Italy), with linear transducer 18MHz, according to the OMERACT 2010. The performance of the methodology was assessed through the area under the ROC curve (Receiver Operating Curve) and p<0.05 was set as significant. Results: Clinically, patients with ND were older, and had more painful joints, longer time of disease, higher enthesitis rate and higher PASI at baseline. According to US assessment, a total of 1232 joints, 672 peripheral enthesis and 1792 tendons were evaluated and synovitis, erosion and tenosynovitis were more frequently found in patients with ND (p<0.02). Lower limbs enthesis were more frequent in Ps patients than HC (39.6% and 9.3%, respectively), especially the GUESS score, regardless ND (p<0.0001). In addition, tendons were thicker in patients than healthy controls, regardless ND (p<0.001), increasing the PsA diagnostic in 41.1%. After 4 years and considering the occurrence of PsA, the PASE was moderately accurate and specific (66% and 68%, respectively), and PEST had high accuracy and specificity for arthritis and dactylitis (73% and 78% vs. 89% and 94%, respectively). Moreover, selfreported dactylitis (OR=17.2; 95% CI 2.235.7; p=0.017) and the GUESS score (p<0.03) were the most important risk factor for predicting PsA after 4year evaluation. Conclusion: There was a significant association between ND and enthesopathy of the distal interphalangeal joint and nail power doppler, evaluated by ultrasound, in patients with psoriasis. Although ultrasound findings of synovitis, erosion and tenosynovitis were more frequent in patients with ND, they were not associated with clinical joint impairment. The final mean GUESS score and selfreported dactylitis were able to predict the occurrence of PsA over 4 years in the adjusted final model.